Baatonum Toponymy of Nigeria-Benin Border Area: Notes on the Methodology of Collecting Toponymic Data - Azibaoguanasi Williams (Вопросы ономастики)
The collection of toponymic data can be a time-consuming, complex, and potentially unproductive process, particularly if not carefully managed. A key challenge lies in failing to engage community members who possess necessary knowledge, typically preserved through oral tradition. Such oversight may lead to inaccurate or disputed results. Identifying such key informants — bearers of historically rooted knowledge — can be especially challenging in unfamiliar sociocultural environments. This paper examines these methodological difficulties, with particular attention to locating informants, documenting toponymic information, and addressing potential resistance or unease among participants. The methodology discussed addresses several challenges inherent in oral history-based linguistic fieldwork. These include (but are not limited to): navigating unfamiliar environments; identifying suitable informants; forming focus groups; maintaining ethical standards to minimize suspicion; managing entry, presence, and departure from the field site; selecting appropriate informants for varying research contexts; and eliciting toponymic data. The article draws on the author’s fieldwork in Baruten, a region on the border between Nigeria and the Republic of Benin in West Africa, and presents part of the data collected. While the approach is grounded in this specific area, it is argued to be adaptable to a range of contexts. Although rural settings may facilitate the elicitation of toponymic legends, the method is equally applicable to urban toponymy and socio-onomastic studies, which often require a synchronic approach.